Urban Infrastructure and governance - Ramesh, G. (ed.) (New Delhi, 2010)
The book contains a selection of papers on urban governance in its multiple perspectives. It has evolved from the presentations made at the Third International Conference on Public Policy and Management held in 2008.The topics are grouped into several themes: Urban Plan and Governance, Urban Governance through Partnership and Participation, and Financing Urban Infrastructure. With several examples from developing nations, the book dwells into the practical and managerial aspects of urban planning, partnerships, participation, financial mobilization and effective governance. One of the highlights of the book is that it looks at financial mobilization as a strategy for governance and how the financial system in itself can be an instrument of governance.
Keywords: Communities